2010
DOI: 10.1007/s00221-009-2143-4
|View full text |Cite
|
Sign up to set email alerts
|

Distorting the visual size of the hand affects hand pre-shaping during grasping

Abstract: Vision of the body is known to affect somatosensory perception (e.g. proprioception or tactile discrimination). However, it is unknown whether visual information about one's own body size can influence bodily action. We tested this by measuring the maximum grip aperture (MGA) parameter of grasping while eight subjects viewed a real size, enlarged or shrunken image of their hand reaching to grasp a cylinder. In the enlarged view condition, the MGA decreased relative to real size view, as if the grasping movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…This suggests that patients may be unable to effectively sense the error with their affected hand and/or subsequently update their motor behavior. Adaptation requires specific sensory inputs: kinesthetic sense from muscle forces used to lift objects is required to produce fingertip load forces appropriate for object weight (Johansson and Westling 1988); tactile sensation from touch receptors is required to produce grip forces appropriate for object texture, with higher grip forces needed to hold smoother objects (Johansson and Westling 1984); and visual input about object contours determines how the hand is shaped during reach (Sakata, Taira et al 1997; Santello and Soechting 1998; Marino, Stucchi et al 2010). In reaching experiments, both vision and proprioception provide information about arm configuration, but faulty integration of visual and proprioceptive signals may introduce errors in motor planning (Gordon, Forssberg et al 1991; Scheidt, Conditt et al 2005; Sarlegna, Przybyla et al 2009); this might explain why we close our eyes when we want to enhance feeling.…”
Section: Forgettingmentioning
confidence: 99%
“…This suggests that patients may be unable to effectively sense the error with their affected hand and/or subsequently update their motor behavior. Adaptation requires specific sensory inputs: kinesthetic sense from muscle forces used to lift objects is required to produce fingertip load forces appropriate for object weight (Johansson and Westling 1988); tactile sensation from touch receptors is required to produce grip forces appropriate for object texture, with higher grip forces needed to hold smoother objects (Johansson and Westling 1984); and visual input about object contours determines how the hand is shaped during reach (Sakata, Taira et al 1997; Santello and Soechting 1998; Marino, Stucchi et al 2010). In reaching experiments, both vision and proprioception provide information about arm configuration, but faulty integration of visual and proprioceptive signals may introduce errors in motor planning (Gordon, Forssberg et al 1991; Scheidt, Conditt et al 2005; Sarlegna, Przybyla et al 2009); this might explain why we close our eyes when we want to enhance feeling.…”
Section: Forgettingmentioning
confidence: 99%
“…Another potential nonvisual cue in visual space perception—the size of the observer—is more difficult to test experimentally (in a within-subjects design) because it would require manipulating the body size of individuals in a laboratory setting. Until recently, the methods that came closest to this requirement altered the apparent size of one’s hand either by zooming in and out on video-recorded displays (Marino, Stucchi, Nava, Haggard, & Maravita, 2010; Pavani & Zampini, 2007) or by using magnifying and minifying goggles (Linkenauger, Ramenzoni, & Proffitt, 2010). It has been shown that such visual distortion of the hand affects both the hand shape during object grasping (Marino et al, 2010) and size perception as measured by a size-matching task (Linkenauger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that body size serves as a fundamental reference in visual perception of object size (28), but also that the combination of information from different visual and oculomotor cues also affects this perception (29). Previous studies have shown, for example, that hand size affects the perceived sizes of external objects (30,31). Besides the size of specific body parts in the perception of the external world, the role of wholebody scaling has also been studied recently.…”
mentioning
confidence: 99%